1981
DOI: 10.1017/s0043174500062081
|View full text |Cite
|
Sign up to set email alerts
|

Common Ragweed (Ambrosia artemisiifolia) Interference in Soybeans (Glycine max)

Abstract: The influence of common ragweed (Ambrosia artemisiifoliaL.) interference on soybean [Glycine max(L.) Merr. ‘Ransom’] yield was studied in the field utilizing naturally occurring weed populations. The damage-threshold population for a full-season, in-row common ragweed infestation was four weeds/10 m of row, which resulted in an 8% yield loss. Soybeans kept weed-free for 2 weeks or longer after emergence in a dry year produced normal yields, but 4 weeks of weed-free maintenance was required when adequate moistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 14 publications
4
67
0
2
Order By: Relevance
“…In soybean ( Glycine max (L.) Merr. ), yield losses of 8% were recorded when four A. artemisiifolia plants m −1 of row were present (Coble et al. , 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In soybean ( Glycine max (L.) Merr. ), yield losses of 8% were recorded when four A. artemisiifolia plants m −1 of row were present (Coble et al. , 1981).…”
Section: Introductionmentioning
confidence: 99%
“…In soybean (Glycine max (L.) Merr. ), yield losses of 8% were recorded when four A. artemisiifolia plants m )1 of row were present (Coble et al, 1981). A. artemisiifolia is also a problem in maize (Zea mays L.) and sunflower (Helianthus annuus L.) (Chollet et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In field studies, variable results in competition experiments repeated over time or space often are attributed to environmental variation (Zimdahl, 1980; Coble et al. , 1981; Hagood et al.…”
Section: Discussionmentioning
confidence: 99%
“…Common ragweed can emerge in late April as soil warms and will continue to emerge until temperatures become unfavorable sending the seeds back into dormancy (Jordan et al, 2014). Coble et al (1981) reported that 0.11 common ragweed/m 2 reduced soybean yield by 32.5 kg/ha on average. When grown in 30% shade, common ragweed has been noted to grow just as well as sweet corn (Zea mays L. var.…”
Section: Introductionmentioning
confidence: 99%